Comparison between intravenous injectable diclofenac and per rectal diclofenac suppository as analgesics in operated per anal and perianal benign pathologies - Deherkar, Juthikaa Abhijit (International Surgery Journal, 2019)
Background: Per anal and perianal surgeries are one of the bread and butter surgeries in a surgeons life, and satisfaction of patient matters a lot. Early miraculous recovery has always been patient’s expectations hence we decided to study standard IV method of diclofenac as analgesic with diclofenac suppository and compared their effects on patients with the help of pain scale of 0 to 10. Methods: 200 common per anal surgeries were considered in the study, and were divided in two groups group A post operatively IV diclofenac was given 12 hourly and in group B cases diclofenac suppository 100 mg was started daily twice and the pain score was noted for a week. Results: Diclofenac suppositories resulted in early pain relief and thus early discharges of these patients. The pain score had decreased to a larger extent by day 3 and was almost negligible by day 5 and a few cases to day 7. The hospital stay reduced as patient could manage suppository at home by themselves. IV site complications like thrombophlebitis leading to pain and fever could be easily avoided. Conclusions: Thus diclofenac suppositories proved to be an effective way to give a pain free satisfaction compared to intravenous painful analgesics, thus decreased their hospital stay and also it was a patient friendly.